Microglial re-modeling contributes to recovery from ischemic injury of rat brain: A study using a cytokine mixture containing granulocyte-macrophage colony-stimulating factor and interleukin-3 - Matsumoto, Shirabe; Choudhury, Mohammed E.; Takeda, Haruna; Sato, Arisa; Kihara, Nanako; Mikami, Kanta; Inoue, Akihiro; Yano, Hajime; Watanabe, Hideaki; Kumon, Yoshiaki; Kunieda, Takeharu; Tanaka, Junya (Frontiers in Neuroscience, 2022)
Ischemic stroke is a leading cause of mortality and permanent disability. Since stroke lesion is chronically and gradually increased due to the secondary neuroinflammation followed by the acute ischemic neuronal degeneration. In this study, a cytokine mixture consisting of granulocyte-macrophage colony stimulating factor (GM-CSF) and interleukin (IL)-3 was evaluated of its ameliorative effect on ischemic brain injury using a rat stroke model prepared by transient (90 min) middle cerebral artery occlusion [tMCAO]). The mixture administration reduced the infarct volume and ameliorated ischemia-induced motor and cognitive dysfunctions. Sorted microglia cells from the ischemic hemisphere of rats administered with the mixture showed reduced mRNA expression for tumor necrosis factor (TNF)-alpha, IL-1beta and inducible nitric oxide synthase at 3 days post-reperfusion. As revealed by flow cytometric analysis, the expression of CD86, a marker for proinflammatory type microglia, was suppressed, and the expression of CD163, a marker for tissue repairing type microglia, was increased by the cytokine treatment. Immunoblotting and immunohistochemistry data showed that the cytokines increased the expression of the anti-apoptotic protein Bcl-xL in both microglia and neurons in the ischemic lesion. Thus, the present study demonstrated that cytokine treatment was remarkably suppressed neurodegeneration during chronic phase in the rat stroke model. The neuroprotective effects may be mediated by increased expression of Bcl-xL in ischemic lesions that presumably lead to phenotypic changes of microglia, while enhancing neuronal survival.